77 HELIOS-A: 18-MONTH EXPLORATORY CARDIAC RESULTS FROM THE PHASE 3 STUDY OF VUTRISIRAN IN PATIENTS WITH HEREDITARY TRANSTHYRETIN-MEDIATED AMYLOIDOSIS. (15th December 2022) - Mussinelli(on Behalf Of The Authors), Roberta; Garcia-pavia, Pablo; Gillmore, Julian D; Kale, Parag; Berk, John L; Maurer, Mathew S; Conceição, Isabel; Dicarli, Marcelo; Solomon, Scott; Chen, Chongshu; Arum, Seth; Vest, John; et al.
Abstract: Background: Hereditary transthyretin-mediated (hATTR) amyloidosis, also known as ATTRv amyloidosis, is a fatal, multisystem disease that presents with progressive polyneuropathy and/or cardiomyopathy. HELIOS-A (NCT03759379) assessed the efficacy of vutrisiran, an investigational RNA interference therapeutic, in patients with hATTR amyloidosis with polyneuropathy. Purpose: To evaluate the effect of 18 months of vutrisiran treatment on exploratory cardiac endpoints in the HELIOS-A Phase 3 study. Methods: Patients were randomised (3:1) to vutrisiran (25 mg SC, q3m) or patisiran (0.3 mg/kg IV, q3w), a reference comparator. The APOLLO placebo group (n=77) was an external control. Primary endpoint was change from baseline in the modified Neuropathy Impairment Score +7 (mNIS+7) at 9 months, vs. external placebo. Exploratory cardiac endpoints included change from baseline in NT-proBNP levels, echocardiography parameters, and technetium (Tc) scintigraphy parameters at 18 months. A prespecified cardiac subpopulation was included (baseline left ventricular wall thickness ≥1.3 cm and no medical history of aortic valve disease or hypertension). Results: HELIOS-A enrolled 164 patients and the primary endpoint was met. In the cardiac subpopulation (n=40/122 vutrisiran; n=36/77 placebo), 18 months of vutrisiran treatment significantly improved NT-ProBNP levels vs. external placebo (adjusted geometric fold change ratio: 0.49; p=0.0004) and demonstrated a trend towards improvement in echocardiographic parameters vs. external placebo (including a significant difference in cardiac output [least squares mean difference: 0.41; p=0.043]). Of the 122 vutrisiran-treated patients, 99mTc scintigraphy assessment was captured for 64 vutrisiran-treated patients at baseline, 35 (54.7%) of whom had Perugini grade ≥2 (moderate/intense) cardiac uptake of 99mTc. Among patients with evaluable scintigraphy parameters repeated at 18 months (evaluable patients), heart-to-contralateral lung ratio and normalised LV total uptake on scintigraphy improved (decrease from baseline) in 64.6% (31/48) and 68.1% (32/47), respectively, at 18 months. Of the evaluable patients, 28.1% (16/57) had an improvement (reduction from baseline) in Perugini grade of cardiac uptake, 68.4% (39/57) had no change in grade, and 3.5% (2/57) worsened in grade. Of evaluable patients with baseline Perugini grade ≥2, the proportion with improvement in heart-to-contralateral lung ratio and normalised LV total uptake was 76.9% (20/26) and 100% (25/25) respectively. No cardiac safety concerns were identified with vutrisiran treatment. Conclusions: In this exploratory analysis, vutrisiran treatment was associated with a positive impact on NT-ProBNP levels and echocardiographic parameters vs. external placebo in the cardiac subpopulation. Vutrisiran treatment also reduced cardiac uptake of 99mTc potentially suggesting reduction in cardiac amyloid, although the clinical significance of this is not yet clear.